Peningkatan Keterampilan Menulis Teks Biografi dengan Menggunakan Model Pembelajaran Problem Based Learning pada Siswa Kelas X SMK Negeri 6 Medan - Setiawan, Heri; Amri, Yusni Khairul; Nadeak, Heppi (Universitas Islam Sumatera Utara, 2025)
This study aims to evaluate the effectiveness of the Problem-Based Learning (PBL) model in enhancing the biography writing skills of Grade X students at SMK Negeri 6 Medan. The research involved 36 students from class X BDP 1 and employed both quantitative and qualitative approaches. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. In Cycle I, the results indicated that students encountered difficulties in composing biographical texts, with an average score of 79.47 and a classical completeness rate of 63.84%. Following reflection and instructional adjustments, Cycle II demonstrated a significant improvement, with the average score increasing to 91.12 and classical completeness reaching 94.45%. The findings confirm that the PBL model positively impacts students’ ability to write biographical texts, demonstrating its effectiveness as a pedagogical strategy in Indonesian language learning. This suggests that PBL facilitates student engagement, critical thinking, and skill development in writing through contextual problem-solving.